Transformasi Limbah Organik Rumah Tangga Menjadi Eco Enzyme sebagai Upaya Pengelolaan Sampah Berbasis Lingkungan - Alifya Shafira; Nova Trisna Dwi Syafitri; Achsani Taqwim; Alfah Fauziah Wardan Azzahro; Faradiva Mutiara Agita; Daffa Aisy Rofif; Lyna Lestari Indrayati (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem of household organic waste management, especially kitchen waste, is still an environmental challenge that has not been handled optimally. In fact, this waste has great potential to be used as environmentally friendly products. One solution that can be applied is the manufacture of eco-enzymes, which are fermented liquids from organic waste that function as a substitute for synthetic chemicals in various household and agricultural purposes. This community service activity aims to increase the awareness and skills of residents in managing organic waste through the creation of eco-enzymes as a tangible form of applying the 3R (Reduce, Reuse, Recycle) principle. The activity was carried out in Kedu Village by involving PKK women, PSRT members, the Farmer Women Group (KWT), and housewives. The methods used include counseling on the impact of household waste and the benefits of eco-enzymes, as well as direct practice of making eco-enzymes accompanied by Mrs. Faila and students of the Real Work Lecture (KKN) of Tidar University. The implementation process includes sorting kitchen waste, mixing fermentation ingredients, and monitoring yields during the incubation period. The results of the activity show that the community is able to understand the concept and techniques of making eco-enzymes well. The active participation of residents in hands-on practice reflects increased knowledge and skills in independent organic waste management. In addition, this activity encourages the formation of new sustainable habits in utilizing household waste, while reducing dependence on synthetic chemicals. Thus, this service makes a positive contribution to environmental conservation efforts and local community empowerment through educational and applicative approaches.